The complete chloroplast genome sequence of Lavandula dentata (Lamiaceae) and its phylogenetic analysis - Hui Li; Jingrui Li; Hongtong Bai; Lei Shi; Huafang Wang (Mitochondrial DNA. Part B. Resources, 2019)
Fringed lavender (Lavandula dentata L., Lamiaceae) is a species of flowering plant commonly grown as an ornamental plant for its finely-toothed leaves, bulrush-like flower spikes, and light-woolly texture. Besides, L. dentata is distinguished by the high percentage of 1,8-cineole and β-pinene in its essential oil, endowing its highly commercial value. The complete chloroplast (cp) genome of L. dentata (GenBank accession number: MK791204) consists of 151,696 bp and includes a pair of inverted repeats (IR) of 25,608 bp separated by the large single copy region (LSC) and small single copy region (SSC) regions of 82,897 and 17,583 bp, respectively. The genome with an overall GC content of 37.9% hosts 114 unique genes including 80 protein-coding genes, 30 tRNA, and four rRNA (rrn5, rrn4.5, rrn16, and rrn23). Phylogenetic analysis of the Lamiaceae based on 16 plastome sequence data gives a hint at the basic structure of the Lamiaceae.